Failure of precalving supplementation of vitamin E and dietary fat to alter reproductive performance of first lactation cows or the health of their calves - Coalson, J.L.; Corah, L.R.; Stokka, Gerald L.; Blecha, Frank (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to determine the effect of precalving supplementation with vitamin E and fat on the reproductive performance of first lactation cows and the health of their calves. Approximately 50 days before the first expected calving, 48 crossbred heifers were allotted to four treatments: 1) basal diet that consisted of 13 lb of prairie hay, 7.3 lb of milo, and 1 lb of supplement per heifer per day; 2) basal diet+supplement bringing the diet to 4% fat; 3) basal diet+supplement providing 1000 IU supplemental vitamin E/day; and 4) basal diet plus both fat and vitamin E. Supplementation of vitamin E and(or) fat had no effect on any reproductive trait in the cows or any immunological measurement in the calves.
Keywords: Beef; Vitamin E; Fat; Reproduction; Calf health